PROSEDUR KHUSUS PELAYANANAN TERPADU FORENSIK KLINIK KORBAN KEKERASAN PEREMPUAN DAN ANAK DI RUMAH SAKIT - Muhammad Kholil Ikhsan; Ahmad Yudianto; Nily Sulistyorini (Jurnal MHKI, 2022)
The Ministry of Women's Empowerment and Child Protection (PPPA) Republic of Indonesia recorded the occurrence of violence against women and children. In the period (1 January - 9 June 2021), there were 2,319 cases of violence against adult women with 2,347 victims and 3,314 cases of violence against children with 3,683 victims. Handling of victims of violence against women (KP) and victims of violence against children (KIA) in hospitals is not yet fully integrated and is similar to other general patient services. Hospital directors and staff must see cases of KP and KIA as cases that should be handled specifically so that victims receive comprehensive services both medically and legally, this paper is expected to be a reference procedure for hospitals that perform clinical forensic services in handling violence against women and children.